The Efforts to Strengthen National Identity Through Ethical Value and Local Wisdom in Oral Literature - Fitrahayunitisna Fitrahayunitisna; Prima Zulvarina (Jurusan Sastra Indonesia, 2017)
Research shows that oral literature contains ethical values and local wisdom. However, the existence of oral literature is getting weaker with the changing of the era. Therefore, to strengthen national identity, oral literature needs to be revived. The main goal is to improve the character of the young generation which is the Z generation. Efforts that need to be done is mediatization of oral literature and integrate oral literature into the college curriculum. The mediatization of oral literature needs to involve digital media, as well as in its dissemination it requires social media. Meanwhile, integration into the college curriculum can be done by insert to the Indonesian language course.